Gender Diversity on the Board of Director and Firm Performance: Agency Theory Perspective - Hindasah, Lela; Harsono, Mugi (Jurnal Manajemen Bisnis, 2021)
Research aims: This paper provides a literature review on the influence of board of directors' gender diversity on financial and non-financial performance.Design/Methodology/Approach: This research used the content analysis identified from previous studies based on the proxies employed. The article selection process was carried out from reputable international journals published in 2017-2020, resulting in 50 articles discussing board gender diversity and performance.Research findings: This study's results are a conceptual model and future research developments. Research related to female directors and performance has been much carried out. Hence, future research suggests correlating female directors based on monitoring characteristics, human capital board, and demographics. The influence of gender diversity on non-financial performance is also rarely studied.Theoretical contribution/Originality: Identification of gender diversity attributes associated with financial and non-financial performancePractitioner/Policy implication: This study provides valuable information for policymakers or regulators to refine future corporate governance policies and increase understanding of the relationship between corporate governance practices and company performance as measured by financial and non-financial performance.Research limitation/Implication: This study is based on only 50 articles in the last four years.